UJI VALIDITAS KONTEN INSTRUMEN KEMAMPUAN REPRESENTASI MATEMATIS DALAM MENYELESAIKAN MASALAH BANGUN DATAR - Zakiyah, Zahra; Kartika, Hendra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
Planar material is one of the materials that will be found again in several subsequent materials. In plane material, students' mathematical representation abilities need to be considered so that students are able to solve problems well. The aim of this research is to analyze the level of validity and reliability of the test instrument for junior high school students' mathematical representation abilities in solving flat shape problems. The research method used is a quantitative descriptive method. By using the Aiken's V formula, the expert validation results obtained an average V value of 0.93, which means that the questions have a very high level of validity and can be used. Meanwhile, the results of the reliability calculation show that the r value is 0.94, which means that the question has a very strong correlation coefficient and can be used. So this instrument can be used by teachers to measure the level of students' mathematical representation abilities in solving flat shape problems.